Privacy in computer ethics: Navigating the digital age - Maxwell Zostant; Robin Chataut (Computer Science and Information Technologies, 2023)
In this digital age, privacy has become a crucial issue due to the vast amount of personal information we share online. As a fundamental aspect of computer ethics, it concerns the appropriate use of information and communication technologies. This paper will discuss five key points related to privacy in computer ethics: the concept of privacy and its significance in the context of computer ethics; ethical considerations surrounding personal information in the digital space, including issues of consent, transparency, and data protection; the legal framework surrounding privacy in different jurisdictions, such as data protection laws and international standards; the role of technology in protecting privacy, including the use of encryption and other security measures; and finally, the challenges associated with protecting privacy in the digital age, such as the risk of data breaches, identity theft, and other forms of online exploitation. Through these five key points, this paper aims to provide a comprehensive understanding of privacy in computer ethics and emphasize the importance of promoting responsible and ethical use of technology.